The Effect of Disaster Training, Social Support and Social Capital on Community Self Efficacy in Dealing With Tsunami Disaster in Pangumbahan Village, Ciracap District, Sukabumi Regency - Iwan Permana (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2022)
There are many factors that influence disaster preparedness, one of which is self-efficacy. Many factors that influence self-efficacy in dealing with disasters include disaster training, social support and social capital. The purpose of this study was to find out what factors affect the community's self-efficacy in dealing with the tsunami disaster. Self-efficacy is an individual's belief in their ability to mobilize motivation, cognitive resources and institutions to exercise control over certain events. This type of research is correlational with a cross sectional approach. The population is the entire community in Pangumbahan Village, Ciracap District, Sukabumi Regency with a sample of 380 people. Sampling using Proportional Random Sampling. The instrument is declared valid & reliable. Data collection using questionnaires and statistical analysis using simple and multiple linear regression. The results showed that there was no significant effect of disaster training on self-efficacy (p-value 0.119), there was a significant effect of social support on self-efficacy (p-value 0.000), social capital on self-efficacy (p-value 0.000). In conclusion, there is an effect of social support and social capital on community self-efficacy in dealing with the tsunami disaster. It is hoped that the community will improve disaster preparedness by participating in various training and disaster simulations & getting involved in disaster-related institutions or organizations. The magnitude of the loss and the number of victims show that the community's preparedness in anticipating the impact of the disaster is still low.